THE KUPOL'NOE SILVER-TIN DEPOSIT (SAKHA REPUBLIC, RUSSIA): AN EXAMPLE OF THE EVOLUTION OF AN ORE-MAGMATIC SYSTEM - Gamyanin G.N.; Alpatov V.V.; Bakharev A.G.; Zhdanov Yu.Ya.; Bortnikov N.S.; Anikina E.Yu.; Nosik L.P.; Borisenko A.S.; Borovikov A.A. (My University, 2001)
A study of temporal relationships and a formation sequence of tin, silver-base metal, and silver-antimony ores; chemical compositions of minerals; fluid inclusions, and stable isotope (S, O, and C) ratios in minerals from the Kupol'noe silver-tin deposit was carried out. The deposit is confined to the Sarychev ring volcano-plutonic structure in the southeast of the Verkhoyansk-Kolyma erogenic belt. It occurs in granodiorites, the Rb-Sr age of which is 125 Ma, and around this granite massif in a hornfel zone. Ore bodies are mineralized cataclastic zones and carbonate-quartz veins with sulfides that are accompanied by greisen, quartz-carbonate-sericite, and argillized rocks. Principal minerals are quartz, carbonates, galena, pyrite, and sphalerite; subordinate minerals are cassiterite, stannite, tetrahedrite, arsenopyrite, and silver-antimony sulfosalts. The deposit was formed as a result of multiply repeated hydrothermal activity. Three types of ore mineralization have been recorded: rare metal (tin-tungsten), tin-silver-base metal, and silver-antimony. The fluid inclusion study showed that the rare metal mineralization was formed from heterogenized fluids with a high chloride content (36-38 wt %) at 250 to 450°C. Major productive carbonate-polysulfide and silver-antimony mineral associations were deposited from low-temperature solutions (125-250°C) with a salinity of 3.3 to 9.2 wt % NaCl-equiv. The δ18O values of quartz I, quartz II, quartz III, and quartz IV are +6.2 to +7.9‰, +7.1 to +8.9‰, +2.3 to +5.5‰, and +8.3 to +11.0‰, respectively. The δ18O and δ13C values of carbonates vary from +17.4 to +29.2‰ and -15.0 to -5.6‰, respectively. The δ34S of sulfides range from -4.2 to +6.0‰. Calculated ratios of oxygen isotopes in water suggest that ore-forming fluids evolved from a fluid with a predominantly magmatic component in which heated meteoric water played a substantial role. A hypothesis on the overprinting of mineralizations deposited in mesothermal and epithermal environments at different stages of geodynamic history of this region is suggested.
Keywords: Verkhoyansk–Kolyma orogenic belt; Kupol’noe silver–tin deposit; Chemical compositions; Fluid inclusions; Isotope ratios